A Study on Rock Paintings in the Yinshan Mountains from the Perspective of Peirce’s Semiotics - Li, Jiaxuan; Dechsubha, Thawascha (Technium Social Sciences Journal, 2023)
The Yinshan rock painting is an extremely important one. A large number of rock paintings in this mountain range record the nomadic life of ancient ancestors and express their emotional beliefs. They show the self feelings of the ancestors by using symbolic figures, animals, celestial bodies, signs and other ways, reflecting the living conditions of the ancestors of various nationalities who once lived in the Yinshan Mountain area. As a “meaningful form” left over from ancient times, the Yinshan rock paintings are signs of human communication of cultural information. Therefore, it is very objective and meaningful to interpret the Yinshan rock paintings from the perspective of semiotics. Charles Sanders Peirce’s semiotics, is an interpretation of meaning, representamen, interpretant. Based on the analysis of Peirce’s definition of signs and the relationship between signs and objects, this paper interprets the Yinshan rock paintings from the perspective of semiotics, explores its rich connotation, and understands the life, belief and historical development of Mongolian ancestors.